Use of sotrovimab in vaccinated versus unvaccinated COVID‐19 patients in a resource‐limited emergency department during the omicron surge - Rahul V. Nene; Melodie A. Santodomingo; Bruce Balog; Hector Martinez; Elias Murillo; Christian A. Tomaszewski; Andrew LaFree (Journal of the American College of Emergency Physicians Open)
Abstract Objective The treatment of outpatient COVID‐19 patients at high risk of disease progression has been challenging, as both the virus and available therapeutics change. Here, we sought to evaluate the effect of vaccination status on the use of sotrovimab during the early phase of the Omicron surge. Methods This was a retrospective observational study performed at El Centro Regional Medical Center, a rural hospital on the southern Californian border. The electronic medical record was queried for all emergency department (ED) patients who received an infusion of sotrovimab between January 6 and February 6, 2022. We obtained patient demographics, COVID‐19 vaccination status, medical comorbidities, and whether patients returned to the ED within 30 days. We stratified our cohort according to vaccination status and performed a multivariable logistic regression model to evaluate the relationship between these factors. Results One hundred seventy patients received an infusion of sotrovimab in the ED. The patient cohort had a median age of 65 years, 78.2% were Hispanic, and obesity (63.5%) was the most common comorbidity. A total of 73.5% of patients were vaccinated against COVID‐19. A total of 12/125 (9.6%) of vaccinated patients returned to the ED within 30 days, versus 10/45 (22.2%) in the unvaccinated cohort, which was statically significant (P = 0.03). The presence of medical comorbidities was not associated with the primary outcome. Conclusion Of patients who received sotrovimab, those who were vaccinated were less likely to return to the ED within 30 days compared to those who were unvaccinated. Given the effectiveness of the COVID‐19 vaccination campaign, and with the emergence of new variants, it is unclear what role monoclonal antibody therapy should play in the treatment of outpatient COVID‐19 patients.